Eventos adversos causados por falhas gerenciais de comunica????o em unidade de terapia intensiva - Quit??rio, L??gia Maria (2014)
The purpose of this study was to investigate patients??? safety incidents that may be associated with management communication failures in Intensive Care Units (ICUs) with the purpose of providing information to develop strategies to increase patient safety and improve the quality of health care. This is an empirical, retrospective study of a descriptive nature, conducted through documental, literature research and action research with a quantitative and qualitative approach to the problem. The study period was from May 25 to August 25, 2009, with a population of 202 admissions of ICU patients from a public hospital, tertiary. We identified 999 patient safety incidents and we analyzed according to the international classification for patient safety (ICPS), with predominance of no harm incidents, with 626 (62.66%), and 248 (24.82%) incidents of harm. Age of patients who have suffered harm incidents was 52.77 years (average, SD = 20.01), with minimum variation of 15 and maximum of 96 years; the average length of stay in the units was 10.09 days (SD = 10.14), ranging from 0 to 70 days. Evaluating the Charlson comorbidity scale incidents by communication failures were more frequent (87.6%) when compared with other incidents (p <0.0005). This finding, can be partially explained, since patients with more comorbidities require intensified nursing care, as well as higher number of medications, more exams requests, so are patients who are more prone to incidents in general, standing out there communication. The incidents with no harm were related to documentation and to verbal communication, generating 62.66% of incidents. Written communication failures were associated to medications, diets and clinical processes and procedures. They accounted for most incidents with harm: 24.82%. In this study, all incidents related to communication failures were of preventable type. We developed a form to be used as a check list to reduce communication incidents that can be employed to improve communication and to increase patient safety in hospitals, especially those related to critical care. The detection of communication incidents were originated at medical prescriptions, nursing controls, medical rounds and nursing care. We identified 152 communication failures, in which 49.67% were related between physicians and the ICU nursing staff. Conclusion: The most observed safety incidents due to communication failure were those related to medications, diets and clinical processes and procedures. All of them were of avoidable type, demonstrating that healthcare manager may have a role in the prevention of patient safety incidents while propose strategies to improve the communication among ICU actors.